Socialism sucks : two economists drink their way through the unfree world - Lawson, Robert, 1967-; Powell, Benjamin, 1978- (Regnery Publishing, 2019)
The bastard step-child of Milton Friedman and Anthony Bourdain, Socialism Sucks is a bar-crawl through former, current, and wannabe socialist countries around the world. Free market economists Robert Lawson and Benjamin Powell travel to countries like Venezuela, Cuba, Russia, and Sweden to investigate the dangers and idiocies of socialism-while drinking a lot of beer.